(untitled) (Revista Sistemas de Producción Agroecológicos, 2011)
The Degree Programme in Agricultural Production, through the course "Elective deepening one," in the livestock line corresponds to the theme of Animal Parasitology, has seen fit to develop a project for the identification of internal anatomical structures ticks Ixodidae family, which have a high prevalence in the Eastern Plains. As a first step, we have done a review of the state of art as classroom experience, this method is intended in context accomplishments achieved more efficiently directed learning processes related to the formation of the student intends to resolve a felt need of the community with observable indicators pose problem by proposing solutions that can be your option for future graduate degree.